(untitled) - Brauer, Roger L. (New York, 1992)
Many organizations waste money on costly construction and renovation projects that do not fit the users' needs. But your organization can eliminate unneeded construction costs and keep large projects on track with the simple but systematic approach to defining building user requirements presented in the second edition of Facilities Planning. The author's approach is applicable to virtually any kind of facility at any stage of planning, and is suitable for small companies or large complex projects in bigger organizations. Both comprehensive and practical, it can be put to immediate use in helping corporate planners, people on facilities committees, and building professionals to differentiate building-user wants from needs; decide to lease, buy, renovate, or sell; improve communication with designers, architects, and contractors; and develop a master plan responsive to changing user needs. Facilities Planning breaks the fundamentals of the user requirements method into easy-to-accomplish tasks, accompanied by worksheets and forms to fill out each step of the way. The book explains how to extract and document critical user data and communicate it to building designers. You'll find ideas for using a computer to manage information on larger, more complex projects, and recommendations for staffing and running the project. To keep readers completely up-to-date on the latest developments in facilities planning, this completely revised edition features new chapters on space management and utilization as well as a glossary of key terms and concepts. "The importance of an orderly, comprehensive method for defining user requirements and packaging them for designers increases with the size and complexity of the project," says the author. With the second edition of Facilities Planning, readers will find a proven method that will satisfy the changing demands of users, planners, and designers, and keep projects on schedule - and under budget.
Keywords: Nhà máy,Factories; Thiết kế và xây dựng,Design and construction